Preemptive Analgesia: No Relevant Advantage of Preoperative Compared With Postoperative Intravenous Administration of Morphine, Ketamine, and Clonidine In Patients Undergoing Transperitoneal Tumor Nephrectomy. Issue 3 (1st May 2002) - Holthusen, Holger; Backhaus, Peter; Boeminghaus, Frank; Breulmann, Maria; Lipfert, Peter
Abstract : Background and Objectives: Preemptive analgesia often failed in the clinical arena because application of a single intravenously applied drug may not prevent nociceptive input and spinal pain processing sufficiently. We therefore used an intravenous (IV), multireceptor approach and tested the preemptive analgesic effect of the antinociceptive drugs morphine, ketamine, and clonidine given before or immediately after surgery. Methods: A double-blind, randomized, prospective study was performed in 30 patients undergoing transperitoneal tumor nephrectomy (via median laparotomy). Standard general anesthesia procedure without opioids was used. After induction, patients were randomly allocated to receive 150 μg · kg −1 of morphine, 150 μg · kg −1 of ketamine, and 5 μg · kg −1 of clonidine intravenously via a motor-driven pump within 15 minutes, either before or immediately after surgery. Patient-controlled analgesia (PCA) with the opioid piritramide (IV) was used for postoperative analgesia. Postoperative pain at rest and during induced cough was quantified by analgesic requirement and pain scores (visual analog scale [VAS]) within 48 hours. Results: There was no significant difference in analgesic requirement of piritramide and pain scores at rest or during induced cough. Conclusions: In contrast to encouraging observations on the combination of antinociceptive drugs, the multireceptor approach tested here failed to exert a clinically relevant effect.